Estimation of carbon stock in Bimbia Bonadikombo coastal community forest, south west region, Cameroon: an implication for climate change mitigation (International Journal of Scientific Research and Management (IJSRM), 2018)
Forests are known to play an important role in regulating the global climate. Nowadays, especially in developing countries wide spread deforestation and forest degradation is continuing unknowingly ad deliberately. This study was conducted to estimate carbon stock in undisturbed research section (Dikolo Penisula) of Bimbia Bonadikombo Community Forest (BBCF). Three transects were created in the research plot and fifteen plots of 10m x10m were laid systematically along each transects, and five sub plots of 1m x1m quadrats were laid within 10m x10m i.e. at the four corners and middle. Trees data (DBH≥2.5cm and Height) were measured in the 10x10m plots. Soil, litter herbs and grass data were collected in the 1x1 m plots. The litters, herbs and grass (LHG) were weighed on the field and evenly mixed and dried at 650C, to determine dry biomass and percentage of carbon. Soil samples were collected at 30cm depth (between 0-10, 10-20, 20-30 cm depths) and density cups was used to determine bulk density and percentage (%) of organic carbon concentration. Allometric equations was use to obtain trees biomass and carbon stock. The results revealed that the total carbon stock was 38.61 t·ha-1. The Soil organic carbon (SOC) was 33.9 t·ha-1 that is 87.8%, while the forest trees stored 2.91 t·ha-1 that is 7.5% of the total carbon. LHGs biomass contributed only1.82t·ha-1 of carbon that is 4.7% of the total carbon stock. The result shows that BBCF is a reservoir of high carbon. To enhance sustainability of the forest potentiality, the carbon sequestration should be integrated with reduced emission from deforestation and degradation (REDD+) and clean development mechanism (CDM) carbon trading system of the Kyoto Protocol to get monetary benefit of CO2 mitigation.